Corrosion behavior and thermos-physical properties of a promising Yb2O3 and Y2O3 co-stabilized ZrO2 ceramic for thermal barrier coatings subject to calcium-magnesium-aluminum-silicate (CMAS) deposition: Experiments and first-principles calculation. (15th April 2021) - Fang, Huanjie; Wang, Weize; Huang, Jibo; Li, Yuanjun; Ye, Dongdong
Highlights: The Yb2 O3 and Y2 O3 co-stabilized ZrO2 towards enhanced CMAS resistance was proposed. Improvement of CMAS resistance owing to a low diffusion rate of Yb 3+ . The first-principles calculation was used to investigate the corrosion behavior. YbYSZ shows better thermo-physical properties as compared with traditional YSZ. Abstract: In this study, corrosion behavior of Yb2 O3 -Y2 O3 co-stabilized ZrO2 (YbYSZ) was systematically investigated under CMAS melt attack. The result was found that YbYSZ exhibited a better CMAS resistance than yttria stabilized zirconia (YSZ), which was attributed to the excellent phase stability. The degradation of grain caused by CMAS attack was greatly related to the diffusion rate of element substantially. Yb 3+ exhibited a low diffusion rate contributing to good phase stability during corrosion. A corresponding first-principles calculation further confirmed this conclusion. Besides, YbYSZ showed a higher thermal expansion coefficient and lower thermal conductivity as compared with YSZ counterpart.